(untitled) (Medico Legal Update, 2020)
Background/Objectives: This study aimed to establish and validate a supportive behavior model for the medication of mothers with children with ADHD based on Theory of Planned Behavior (TPB) and empirical evidence. Method/Statistical Analysis: Participants were 205 mothers with children in elementary school in grades 1 to 3 who had been diagnosed with ADHD and experienced medication treatment. A constructed Structural Equation Model (SEM) was analyzed using AMOS program. Findings: The goodness-of-fit index of the final model was found to be appropriate. The model’s explanatory power for mother’s medication supportive behavior was 90.4%. The intention for medication supportive behavior (? = .486, p<.001), subjective norms (? = .250, p<.001), the perceived control for the medication supportive behavior (? = .287, p<.001) and psychological health of mothers (? = -.074, p = .008) had a direct effect on medication supportive behavior. Mothers’ ADHD knowledge (? = .060, p = .016) was found to have an indirect effect on medication supportive behavior. Improvements/Applications: The results of this study are expected to guide the development of interventions to improve the medication compliance rate of ADHD children in lower academic years in elementary school.